Synergistic effects of 5-aminolevulinic acid based photodynamic therapy and celecoxib via oxidative stress in human cholangiocarcinoma cells - Kim CH (Dove Medical Press, 2013)
Cy Hyun Kim,1,2,* Chung-Wook Chung,1,* Hye Myeong Lee,1 Do Hyung Kim,1,2 Tae Won Kwak,1 Young-IL Jeong,1 Dae Hwan Kang1,21National Research and Development Center for Hepatobiliary Cancer, Research Institute for Convergence of Biomedical Science and Technology, Yangsan, Republic of Korea; 2School of Medicine, Pusan National University Yangsan Hospital, Yangsan, Republic of Korea*These authors contributed equally to this workAbstract: 5-Aminolevulinic acid (ALA)-based photodynamic therapy (PDT) has the potential to kill cancer cells via apoptotic or necrotic signals that are dependent on the generation of intracellular reactive oxygen species (ROS). Celecoxib is an anti-inflammatory drug that induces intracellular ROS generation. We investigated whether the combined application of celecoxib and ALA-PDT improved the efficacy of PDT in human cholangiocarcinoma cells and in tumor bearing mice. In vitro, combined treatment of celecoxib and ALA-PDT increased phototoxicity and intracellular ROS levels after irradiation with 0.75 J/cm2 when compared to ALA-PDT alone. Even though ROS levels increased with 0.25 J/cm2 of irradiation, it did not influence phototoxicity. When heme oxygenase-1, a defensive protein induced by oxidative stress, was inhibited in the combined treatment group, phototoxicity was increased at both 0.25 J/cm2 and 0.75 J/cm2 of irradiation. We identified the combined effect of ALA-PDT and celecoxib through the increase of oxidative stress such as ROS. In vivo, about 40% tumor growth inhibition was observed with combined application of ALA-PDT and celecoxib when compared to ALA-PDT alone. The combined application of ALA-PDT and celecoxib could be an effective therapy for human cholangiocarcinoma. Moreover, use of a heme oxygenase-1 inhibitor with PDT could play an important role for management of various tumors involving oxidative stress.Keywords: celecoxib, aminolevulinic acid, reactive oxygen species, photodynamic therapy, human cholangiocarcinoma